KAJIAN KINERJA PENGELOLAAN RUMAH SUSUN SEWA OLEH PEMERINTAH PUSAT, PEMERINTAH DAERAH, DAN BUMN DI DKI JAKARTA - Yuli Arianto, Bagus; Tresani, Nurahma; Mahmud, Nasiruddin (Universitas Tarumanagara, 2024)
The increase in Jakarta's population has led to a pressing need for adequate housing. The government responded by facilitating the construction of apartment buildings, especially for Low-Income Communities (MBR). According to Government Regulation No. 13 of 2021, Article 15, the provision of apartment buildings can be carried out by various parties, including the Central Government, Local Governments, State-Owned Enterprises (BUMN), and private entities. This study selected three apartment buildings: Rempoa Apartment (managed by the Ministry of Public Works and Public Housing), Cipinang Muara Apartment (managed by the Jakarta Provincial Government), and Seruni Apartment (managed by Perumnas). Each has different characteristics, including their sources of funding. The aim of this research is to identify the performance of each manager and evaluate the strengths and weaknesses of their management. The methods used are Servqual and Importance Performance Analysis (IPA) to assess residents' perceptions of the management performance of the apartment buildings. The evaluation results show that Cipinang Muara Apartment has superior performance in all evaluated dimensions, followed by Seruni Apartment and Rempoa Apartment. This study has the potential to benefit apartment building operators, residents, and other researchers by improving management optimization, participation, and contribution to program development and further research. It is hoped that the results of this research will enhance understanding of the effectiveness of apartment building management and inspire further improvement and development in providing adequate housing for MBR in Jakarta. Keywords: Rental flats; Management performance; Servqual; IPA Abstrak Peningkatan jumlah penduduk di Jakarta telah memunculkan kebutuhan mendesak akan hunian yang layak. Pemerintah merespons dengan memfasilitasi pembangunan rumah susun, terutama untuk Masyarakat Berpenghasilan Rendah (MBR). Berdasarkan Peraturan Pemerintah No. 13 tahun 2021 pasal 15, penyelenggaraan rumah susun dapat dilakukan oleh berbagai pihak, termasuk Pemerintah Pusat, Pemerintah Daerah, Badan Usaha Milik Negara (BUMN), dan swasta. Penelitian ini memilih tiga rumah susun, yaitu Rusunawa Rempoa (dikelola oleh Kementerian PUPR), Rusunawa Cipinang Muara (dikelola oleh Pemerintah DKI), dan Rusunawa Seruni (dikelola oleh Perumnas). Ketiganya memiliki karakteristik yang berbeda, termasuk sumber dana pengelolaannya. Tujuan penelitian ini adalah mengidentifikasi kinerja masing-masing pengelola serta mengevaluasi kelebihan dan kekurangan pengelolaannya. Metode yang digunakan adalah Servqual dan Importance Performance Analysis (IPA) untuk mendapatkan penilaian dari penghuni terhadap kinerja pengelolaan rumah susun. Hasil evaluasi menunjukkan bahwa Rusunawa Cipinang Muara memiliki kinerja unggul dalam semua dimensi yang dievaluasi, diikuti oleh Rusunawa Seruni dan Rusunawa Rempoa. Penelitian ini berpotensi memberikan manfaat bagi penyelenggara rumah susun sewa, penghuni, serta peneliti lainnya dengan meningkatkan optimalisasi pengelolaan, partisipasi, dan kontribusi dalam pengembangan program serta penelitian selanjutnya. Diharapkan hasil penelitian ini dapat meningkatkan pemahaman tentang efektivitas pengelolaan rumah susun, serta menginspirasi perbaikan dan pengembangan lebih lanjut dalam penyediaan hunian yang layak bagi MBR di Jakarta.